Bibliometric review of Malaysian Journal of Library and Information Science 1996-2019 / Muslim Ismail@Ahmad, Roslina Othman and Mohd Nasir Ismail - Ismail@Ahmad, Muslim; Othman, Roslina; Ismail, Mohd Nasir (2020)
Scopus database was used in this journal bibliometric review of the Universiti Malaya based journal, the Malaysian Journal of Library and Information Science, (MJLIS). This research presented data analysis of authors' productivity, highest cited papers, documents by country, documents affiliations, and documents funding sponsor. This paper is inspired by bibliometric method and studies particularly in the context of Malaysian bibliometrician specifically those of Tiew, Abrizah, and Kiran, (2002). Based on co-word analysis MJLIS has produced 415 documents from 1996 to 2019, mainly on bibliometric studies, Malaysia, scientometrics, and academic libraries. In this research, VOSviewer was used to analyze citation network in MJLIS papers and identify high cited papers in the citation network.